The mediating effect of self-efficacy on career aspiration and organizational support with subjective career success among Malaysian women managers during the Covid-19 pandemic - Hamzah, Siti Raba'ah; Musa, Siti Nur Syuhada; Mohamad, Norhazlina (Frontiers Media, 2022)
The lives and jobs of many people have been negatively affected by the Covid-19 pandemic. Lockdowns to curb the pandemic have resulted in many people having to work from home. The question that arises is whether women's jobs are more vulnerable to the crisis. In this regard, it would be useful to understand the factors that affect career success, specifically that of Malaysian women managers. The present study sought to examine the impact of career aspiration and organizational support on subjective career success, as well the mediating role of self-efficacy in these relationships. The participants comprised 146 Malaysian women managers who had completed an occupational self-efficacy scale, career aspiration scale, as well as perceived organizational support and subjective career success inventory. The results of multiple linear regression indicated that those with high levels of career aspiration and perceived organizational support were positively associated with subjective career success. In this connection, self-efficacy mediated both relationships. The findings provided a better understanding of women managers' perception of career success in the service sector.